Coupling of 2D discretized Peridynamics with a meshless method based on classical elasticity using switching of nodal behaviour. Issue 5 (3rd July 2017) - Shojaei, Arman; Zaccariotto, Mirco; Galvanetto, Ugo
Abstract : Purpose: The paper aims to use a switching technique which allows to couple a nonlocal bond-based Peridynamic approach to the Meshless Local Exponential Basis Functions (MLEBF) method, based on classical continuum mechanics, to solve planar problems. Design/methodology/approach: The coupling has been achieved in a completely meshless scheme. The domain is divided in three zones: one in which only Peridynamics is applied, one in which only the meshless method is applied and a transition zone where a gradual transition between the two approaches takes place. Findings: The new coupling technique generates overall grids that are not affected by ghost forces. Moreover, the use of the meshless approach can be limited to a narrow boundary region of the domain, and in this way, it can be used to remove the "surface effect" from the Peridynamic solution applied to all internal points. Originality/value: The current study paves the road for future studies on dynamic and static crack propagation problems.